2014
DOI: 10.1007/s10969-014-9172-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural genomics studies of human caries pathogen Streptococcus mutans

Abstract: Gram-positive bacterium Streptococcus mutans is the primary causative agent of human dental caries. To better understand this pathogen at the atomic structure level and to establish potential drug and vaccine targets, we have carried out structural genomics research since 2005. To achieve the goal, we have developed various in-house automation systems including novel high-throughput crystallization equipment and methods, based on which a large-scale, high-efficiency and low-cost platform has been establish in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…We show for the first time a quantitative study of the total expression and solubility of thirty proteins from a psychrotolerant organism. We found that 50% of the expressed proteins could be classified as soluble, being this value remarkably similar to that previously described for proteins of thermophilic and mesophilic organisms 11 , 12 . In addition, we evaluated the influence of different factors, known to modulate heterologous protein production, on the experimental expression and solubility of our dataset.…”
Section: Introductionsupporting
confidence: 88%
“…We show for the first time a quantitative study of the total expression and solubility of thirty proteins from a psychrotolerant organism. We found that 50% of the expressed proteins could be classified as soluble, being this value remarkably similar to that previously described for proteins of thermophilic and mesophilic organisms 11 , 12 . In addition, we evaluated the influence of different factors, known to modulate heterologous protein production, on the experimental expression and solubility of our dataset.…”
Section: Introductionsupporting
confidence: 88%
“…The systematic use of selenomethionine as an anomalously scatterer that could be readily incorporated into proteins as a powerful agent for obtaining crystallographic phases has dramatically changed structural biology and greatly contributed to the vision and realization of Structural Genomics [72]. The development of algorithms for automatic interpretation of macromolecular diffraction data and generation of atomic, combined with the extensive automation in gene sequencing and the beginnings of automation in gene cloning and protein expression suggested to many that ever more automated and rapid structure determination could be carried out [182, 183, 184, 185, 186]. …”
Section: Recent and Future Perspectives: Structural Genomics And X-ramentioning
confidence: 99%
“…We have applied the SG approaches to the structural and functional characterization of proteins from a dental caries pathogen Streptococcus mutans . Using the platform, we have cloned about 1,400 genes encoding non-membrane proteins from S. mutans genome containing 1963 ORFs [183, 203] into a variety of pET vectors using mainly conventional cloning techniques. We then over-expressed and purified soluble proteins by using an E. coli expression system.…”
Section: Recent and Future Perspectives: Structural Genomics And X-ramentioning
confidence: 99%